Mediastinal cryptococcoma as part of disseminated cryptococcosis in HIV-negative pregnant woman with Myasthenia Gravis: Autopsy case report - Bianca Ponnamma Samy; Nosipho Maria Thobakgale; Moshawa Calvin Khaba (Medical Mycology Case Reports)
Cryptococcosis is a fungal infection commonly found in immunocompromised individuals, but it can also affect immunocompetent individuals. A pregnant woman with myasthenia gravis, HIV-negative, died after a diagnosis of tuberculosis. An autopsy revealed a mediastinal mass and organ involvement, indicating a disseminated cryptococcal infection. This case highlights the importance of maintaining a high index of suspicion for cryptococcal infection in immunosuppressed individuals, even without HIV/AIDS. Early detection is achieved by measuring serum cryptococcal antigen.